2007
DOI: 10.1159/000099988
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Low- to Intermediate-Grade Chondrosarcoma of the Thumb with Lung Metastases: An Objective Response to Trofosfamide

Abstract: Low- to intermediate-grade chondrosarcoma is usually a slow-growing and highly chemotherapyresistant tumor type. Case Report: The 76-year-old female patient presented with low- to intermediate-grade chondrosarcoma of the distal phalanx of the right thumb in 1993 and was treated with an excision of the carpometacarpal joint. Approximately 10 years later, the patient presented with recurrent local disease at the trapezoid bone, which was resected. Eight months later she presented with local recurrence at the car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…In the hand, the distribution for site in enchondroma and chondrosarcoma is similar [10]. Although the relationship between the two conditions is difficult to ascertain, the possibility of chondrosarcoma of the hand arising from solitary pre-existing enchondroma has been rarely documented [11][12][13]. This event justifies in our opinion systematic histological investigation of all suspected enchondromata.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In the hand, the distribution for site in enchondroma and chondrosarcoma is similar [10]. Although the relationship between the two conditions is difficult to ascertain, the possibility of chondrosarcoma of the hand arising from solitary pre-existing enchondroma has been rarely documented [11][12][13]. This event justifies in our opinion systematic histological investigation of all suspected enchondromata.…”
Section: Discussionmentioning
confidence: 78%
“…The metastatic rate in digital chondrosarcoma is extremely low in contrast to chondrosarcoma located elsewhere but this event has been reported [3,5,11,17]. For this reason in our opinion, after surgical treatment of hand chondrosarcoma, the patients have to be followed with careful and prolonged postoperative surveillance.…”
Section: Discussionmentioning
confidence: 91%
“…However, some cases, as reported in the literature, showed local recurrence and could metastasize. 7 Little is known about the biological behaviour of phalangeal chondrosarcoma and controversial data are reported in the literature. 8–13 Bovèe et al 8 have previously reported that Evans’ grading could not be applied to chondrosarcoma of the hand in predicting disease-free survival, because it appears to display a different behaviour from chondrosarcomas located elsewhere in the body.…”
Section: Discussionmentioning
confidence: 99%
“…Metastases of reverse direction also seem to exist. Debruyne et al 50 had reported on a 76-year-old female who presented with chondrosarcoma of the distal right thumb. Ten (10) years after the surgery, the disease recurred at the trapezoid bone, followed by carpal joint and lung metastases.…”
Section: Connections Beyond Congenital Malformations-"metastases"mentioning
confidence: 99%